2015
DOI: 10.1007/s40544-015-0094-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bearing, gears and gearboxes performance with different wind turbine gear oils

Abstract: Abstract:The oil viscosity specification for wind turbine gear oils is ISO VG 320, although there are quite different viscosity indexes oils for that viscosity specification. This work evaluates the behaviour of different base oil formulations, since polyalphaolefin (PAO), mineral, ester and polyalkeleneglycol (PAG) that withstand quite different viscosity indexes. The oils evaluation was done in rolling bearing tests and gear tests. Their behaviour was compared for operating conditions in the range observable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Other experimental evidence of scale effects is found in Refs. [6,7]. Ciulli [6] investigated the effect of contact scale on the EHL traction and film thickness by doing measurements with a ball-on-disc machine using three balls in different diameters.…”
Section: Introductionmentioning
confidence: 99%
“…Other experimental evidence of scale effects is found in Refs. [6,7]. Ciulli [6] investigated the effect of contact scale on the EHL traction and film thickness by doing measurements with a ball-on-disc machine using three balls in different diameters.…”
Section: Introductionmentioning
confidence: 99%
“…However, the simplest way to reduce the power losses of an already existing gearbox is to act on the lubricant. Several studies have shown how different lubricants influence efficiency . Despite the great availability of data regarding the relation between lubricant and efficiency, literature is lacking with respect to the effect of the static pressure on the power losses.…”
Section: Power Losses and Efficiency In Gearsmentioning
confidence: 99%
“…Several studies have shown how different lubricants influence efficiency. [17][18][19][20][21][22][23] Despite the great availability of data regarding the relation between lubricant and efficiency, literature is lacking with respect to the effect of the static pressure on the power losses. For this reason, the present research has been focused quantify this effect of the static pressure on efficiency.…”
Section: Power Losses and Efficiency In Gearsmentioning
confidence: 99%
“…Numerous research works have discussed the inevitability of load-dependent [13][14][15] and independent power loss [16][17][18] in gear drives, as the contact load will majorly disturb the load-dependent power loss in the drive by the influence of contact stress and sliding friction during contact in toothed gearing 19 system. Due to this, it is vital to estimate the varying friction coefficient 20,21 along the contact path.…”
Section: Introductionmentioning
confidence: 99%